2009
DOI: 10.1021/ic9018376
|View full text |Cite
|
Sign up to set email alerts
|

The Side-On Copper(I) Nitrosyl Geometry in Copper Nitrite Reductase Is Due to Steric Interactions with Isoleucine-257

Abstract: Density functional theory calculations were used to investigate the binding mode of copper(I) nitrosyl (Cu(I)-NO) in copper nitrite reductase (CuNIR). The end-on Cu(I)-NO geometry (2) was found to be the global energy minimum, while the side-on binding mode (1) corresponds to a local minimum. Isoleucine-257 severely interacts sterically with the Cu(I)-NO unit when bound end-on but not in the side-on case. In addition, the side-on geometry is also stabilized by a hydrogen bond between aspartic acid-98 and NO, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
52
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(60 citation statements)
references
References 13 publications
8
52
0
Order By: Relevance
“…Third, cryogenic manipulations for reducing radiation damages in SRX have also been focused as a factor that changes the population of amino acid residues (33, 34) and enzyme-substrate complexes (35). Crystallographic (36), computational (37), and spectroscopic (38-40) studies actually show that binding modes of NO 2 − and NO in CuNiR crystal structures can differ from those in physiological environments.…”
Section: Significancementioning
confidence: 99%
See 1 more Smart Citation
“…Third, cryogenic manipulations for reducing radiation damages in SRX have also been focused as a factor that changes the population of amino acid residues (33, 34) and enzyme-substrate complexes (35). Crystallographic (36), computational (37), and spectroscopic (38-40) studies actually show that binding modes of NO 2 − and NO in CuNiR crystal structures can differ from those in physiological environments.…”
Section: Significancementioning
confidence: 99%
“…A conundrum remained: Which Cu-NO species is produced in the enzymatic cycle (VI)? Whereas side-on NO is stabilized in crystal structures (22,23,25), spectroscopic and computational studies indicate that end-on NO is a physiological intermediate (37)(38)(39)(40). Although visualization of an end-on NO species with short lifetime has been difficult, time-resolved SFX may enable it (60,61).…”
mentioning
confidence: 99%
“…The crystal structure of A. faecalis S6 Nir obtained by soaking ascorbate-reduced single crystals with NO-saturated buffer and that of as-isolated A. cycloclastes Nir with an endogenous NO ligand showed an unexpected side-on coordination of NO to Cu(I), in contrast to the end-on configuration adopted by NO in copper inorganic complexes [46]. Distinct DFT studies showed that interactions with amino acid side chains are responsible for causing the unusual side-on orientation in Nirs [46,[48][49][50][51]. Copper-nitrosyl adducts present S = 1/2 ground state associated with nearly axial EPR signals (g iso~2 ) and with fast relaxing behavior [46].…”
Section: Epr Characterization Of the Copper Centersmentioning
confidence: 96%
“…Recent calculations by Merkle and Lehnert which include the second sphere residues Asp98 and Ile289 show that the side-on bound geometry is a local minimum while the end-on geometry is the global minimum, with a small barrier of 1.0 kcal/mol required for conversion from the side-on to the end-on structure. 1267 Interactions that contribute to stabilizing the side-on coordination geometry include hydrogen bonding from Asp98, which is 1–2 kcal/mol stronger in the side-on case, and steric constraints from Ile289, which restricts the geometry of the end-on NO complex. Thus, the side-on coordination of the CuNiR NO complex observed in crystals may represent a metastable form that relaxes to end-on coordination in solution when the positions of the sidechains of Ile289 and Asp98 are more flexible.…”
Section: 0 Copper Sites In Bacterial Denitrificationmentioning
confidence: 99%